Kikuchi-Fujimoto Disease in Pediatrics - Erna Kristiani; Selina Natalia; Elizabeth Victoria Fedora Ritonga; Stanislaus Djokomuljanto; Erick Fransisco Kan (Elsevier, 2021)
Background: Kikuchi-Fujimoto Disease (KFD)11 KFD: Kikuchi-Fujimoto Disease. is a rare, benign, idiopathic, and self-limiting lymphadenitis typically affecting head and neck regions. It was first reported in 1972 in Japan, and seldomly reported in children. KFD may mimic diseases like lymphoma, autoimmune conditions, tuberculosis, and other diseases. There are no available specific diagnostic laboratory tests for diagnosing KFD. Histopathologic and immunohistochemistry study is the only tool to establish definite diagnosis. So, diagnosing KFD can be a challenge, especially in pediatric population. Case presentation: Here we describe three cases of KFD presenting to our hospital in Indonesia within 5 years. The first case demonstrated a rare case of KFD complicated with Systemic Lupus Erythematosus; the second case with relapsed pulmonary Tuberculosis; and the third case with multiple lymphadenopathies without any other symptoms. All three cases presented with specific immunochemistry results for KFD. Conclusion: Kikuchi-Fujimoto disease remains a challenge for clinicians and pathologists to diagnose. There are no clear diagnostic criteria. Clinicians must be aware of KFD in patients with prolonged fever and lymphadenopathy. Pathologist should be familiar with KFD morphology to avoid misdiagnosis and unnecessary treatments. Other differential diagnoses should be ruled out, especially tuberculosis where it is highly prevalent in Indonesia.